UJI KANDUNGAN GIZI DAN ORGANOLEPTIK KERIPIK KULIT MELINJO BERDASARKAN VARIASI BUMBU DAN LAMA PERENDAMAN - Eny Idayati (Politeknik Pertanian Negeri Kupang, 2008)
Analysis of Organoleptic and Nutrient Content in Rind Flaky of Melinjo. The aim of this research was to find out the best combination of condiment and lengthy soaking time to produce nutritious rind flaky of melinjo and preferred by consumer. The method applied was completely randomized design. The treatments were two factors that are condiment mixture and lengthy soaking time. The condiment mixture consisted of garlic 2% and coriander 1%, garlic 3% and coriander 2%, garlic 4% and coriander 3%. The lengthy soaking time consisted of 20 minutes, 120 minutes, and 20 minutes. There were three replications in each treatment. Data observed was analyzed using analysis of variance (ANOVA) and least significant difference (LSD) test at level 0,05. Experimental parameters were measured in first analysis of fresh curries and final analysis of rind flaky of melinjo. Those parameters were the contents of calorie, water, carbohydrate, fat, and vitamin A. Organoleptic test (using sensoric method) was executed by semi trained panelist, covered taste, color, texture, and aroma. The result showed that the condiment mixture of garlic 3% and coriander 2% with lengthy soaking time of 20 minutes was the best characteristic of rind of melinjo. Â Keywords: condiment variation, soaking, melinjo's skinned flaky, organoleptik